The lipide soluble vitamin contents of some Onobrychis Miller (Fabaceae) taxa - Emre, Irfan; Sepet, Hakan; Kurşat, Murat; Bahsi, Muammer; Ökkeş,; Yılmaz, Okkes; Şahin, Ahmet (My University, 2019)
The goal of this study is to determine the lipid-soluble vitamin contents in seeds of the someOnobrychis Miller (Fabaceae) taxa by using HPLC. Samples were collected from the natural habitats.Studied materials were dissolved in acetonitrile/methanol (75/25 v/v) and were injected 50 ?L to HPLCinstrument (Shimadzu, Kyota Japan). According to data obtained from present study showed that O.hypargyrea, O. viciifolia, O. caput-galli, O. fallax and O. oxyodonta var. armena have high lipide-solublevitamin contents. Present study found that O. oxyodonta var. armena (1777.27±6.24 µg/g), O. fallax(916.0±4.51 µg/g) O. hypargyrea (809.7±5.03 µg/g) and O. viciifolia (399.7±3.54 µg/g) have highestbeta-caroten content. Also, O. caput-galli has high beta caroten content (73.3±.94 µg/g). on the otherhand, it was found that O. fallax has highest gamma-tocopherol content (1401.2±8.76 µg/g). O.viciifolia (574.9±2.35 µg/g), O. caput-galli (410.1±4.56 µg/g), O. oxyodonta var. armena (267.7±3.68µg/g), O. podporea (162.5±2.14 µg/g) were the other high gamma tocopherol content. Whereas,retinol, retinol acetate and r-tocopherol contents were found absent or trace amounts in the presentstudy.
Keywords: Biyoloji; Kimya; Tıbbi